MANAJEMEN ASET DAERAH (ANALISIS PERALIHAN FUNGSI BANGUNAN DI LINGKUNGAN PEMERINTAH KABUPATEN BADUNG) - Elinda Suryani, Pande Made; Erviantono, Tedi; Winaya, I Ketut (CITIZEN CHARTER, 2015)
ABSTRACT Management asset instructed can guarantee development of going concern capacities of local government, so that claimed to be can develop orÂ  optimal of exploiting of area asset utilize to improve earnings of area genuiness. To be able to be optimal of asset property of area, hence require to be conducted by exploiting of asset, where this matter is happened at Government Sub-Province of Badung with Government Town of Denpasar. Such as those which have been known, that in this time Government Town of Denpasar is exploiting building real property property of Government Sub-Province of Badung which located in Lumintang, where which we know that the farm unifinished previously for no exploiting it. To see the the problems hence intention of this research is to know management pattern exploiting of area asset switchover of building function in environment Governmental Sub-Province of Badung. This research use method of descriptive qualitative. Where to get data, researcher conduct observation seen directly phenomenon that happened field and also circumstantial interview with guest speaker related to Management Asset Area (Analyse switchover of building function in environment Government Sub-Province of Badung).Obtained conclusion of this research is Government Sub-Province of Badung not yet too is applying of principle of akuntabilitas and transparency in area asset management, where this matter proven by there is still its is problem of related to used exploiting form between Government Sub-Province of Badung with Government Town of Denpasar in exploiting of asset of ex-Center Governance of Sub-Province of Badung and also there is still its of resistances that happened in management of asset in Sub-Province of Badung so that government cannot give accurate information and detailed about assets property of Government Sub-Province of Badung especially regarding asset remain to property of Government Sub-Province of Badung to society Â  Keyword : Management Asset Area, Exploiting of Asset